1999
DOI: 10.1097/00004728-199911000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cystic Tumors of the Pancreas: CT Accuracy

Abstract: As patients with previous history of pancreatitis were excluded from the study, CT findings allowed correct characterization of only 60% of cystic pancreatic masses. Among the remaining 40%, 15-20% of the wrong diagnoses could not be corrected by means of CT, given the patterns shown by the tumors. In 20-25% of the cases, a nonspecific diagnosis of cystic mass was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(91 citation statements)
references
References 36 publications
3
85
0
3
Order By: Relevance
“…Recent medical literature has reported the incidence of an accurate diagnosis of SCA based on imaging studies to vary from 27.2% to 77.7% [9][10][11] Of greater concern is the potential misdiagnosis of a malignant neoplastic mucinous cyst as an SCA, an event that was reported to occur in 7 of 28 patients in 1 study 9 and in 2 of 49 patients in another. 10 The high proportion of macrocystic SCA (24%), which is notoriously more difficult to diagnose, may explain the relatively low accuracy of cross-sectional imaging noted in the current study. It should also be noted that the current study, with a high percentage of surgically resected SCAs, was biased toward SCAs with an atypical imaging appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent medical literature has reported the incidence of an accurate diagnosis of SCA based on imaging studies to vary from 27.2% to 77.7% [9][10][11] Of greater concern is the potential misdiagnosis of a malignant neoplastic mucinous cyst as an SCA, an event that was reported to occur in 7 of 28 patients in 1 study 9 and in 2 of 49 patients in another. 10 The high proportion of macrocystic SCA (24%), which is notoriously more difficult to diagnose, may explain the relatively low accuracy of cross-sectional imaging noted in the current study. It should also be noted that the current study, with a high percentage of surgically resected SCAs, was biased toward SCAs with an atypical imaging appearance.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the presence of haemorrhaging and necrosis, even when a thick capsule exists. 3,7 That is why it can be confused with pseudocyst of pancreas as in our case. Grossly e mostly the neoplasms present as large, round, solitary masses (average size 8e10 cm), and are often fluctuant.…”
Section: Discussionmentioning
confidence: 63%
“…Occasionally, the haemorrhagic-cystic changes involve almost the entire lesion so that the neoplasm may be mistaken for a pseudocyst. 6,7 The tumour wall may contain calcifications. Though unusual multicentric or extrapancreatic (mesocolonic, retroperitoneal, omental, hepatic) presentation have been reported, metastasis is rare.…”
Section: S6mentioning
confidence: 99%
“…Microcystic serous cystadenoma appears like a "honeycomb" with a typical central calcification named "central scar." However, less common macrocystic variants may be more difficult to differentiate from a mucinous tumor, with several studies having shown that CT is discriminatory in less than half of the cases [5,6]. When tomographic imaging is not able to provide a proper specific characterization, endoscopic ultrasound (EUS) and cyst fluid aspiration have been recommended as useful diagnostic techniques.…”
Section: Serous Cystic Neoplasmmentioning
confidence: 99%